Patients' Experiences of Web-Based Access to Electronic Health Records in Finland: Cross-sectional Survey - Sari Kujala; Iiris Hörhammer; Akseli Väyrynen; Mari Holmroos; Mirva Nättiaho-Rönnholm; Maria Hägglund; Monika Alise Johansen (JMIR Publications, 2022)
BackgroundPatient portals that provide access to electronic health records offer a means for patients to better understand and self-manage their health. Yet, patient access to electronic health records raises many concerns among physicians, and little is known about the use practices and experiences of patients who access their electronic health records via a mature patient portal that has been available for citizens for over five years. ObjectiveWe aimed to identify patients' experiences using a national patient portal to access their electronic health records. In particular, we focused on understanding usability-related perceptions and the benefits and challenges of reading clinical notes written by health care professionals. MethodsData were collected from 3135 patient users of the Finnish My Kanta patient portal through a web-based survey in June 2021 (response rate: 0.7%). Patients received an invitation to complete the questionnaire when they logged out of the patient portal. Respondents were asked to rate the usability of the patient portal, and the ratings were used to calculate approximations of the System Usability Scale score. Patients were also asked about the usefulness of features, and whether they had discussed the notes with health professionals. Open-ended questions were used to ask patients about their experiences of the benefits and challenges related to reading health professionals' notes. ResultsOverall, patient evaluations of My Kanta were positive, and its usability was rated as good (System Usability Scale score approximation: mean 72.7, SD 15.9). Patients found the portal to be the most useful for managing prescriptions and viewing the results of examinations and medical notes. Viewing notes was the most frequent reason (978/3135, 31.2%) for visiting the portal. Benefits of reading the notes mentioned by patients included remembering and understanding what was said by health professionals and the instructions given during an appointment, the convenience of receiving information about health and care, the capability to check the accuracy of notes, and using the information to support self-management. However, there were challenges related to difficulty in understanding medical terminology, incorrect or inadequate notes, missing notes, and usability. ConclusionsPatients actively used medical notes to receive information to follow professionals' instructions to take care of their health, and patient access to electronic health records can support self-management. However, for the benefits to be realized, improvements in the quality and availability of medical professionals' notes are necessary. Providing a standard information structure could help patients find the information they need. Furthermore, linking notes to vocabularies and other information sources could also improve the understandability of medical terminology; patient agency could be supported by allowing them to add comments to their notes, and patient trust of the system could be improved by allowing them to control the visibility of the professionals' notes.